PERCEPTIONS AND EXPERIENCES OF SENIOR ENGLISH TEACHERS INTEGRATING ARTIFICIAL INTELLIGENCE INTO ELT PRACTICES - Tsabitha Asfarina Putri; Yeny Prastiwi (Universitas Duta Bangsa Surakarta, 2026)
The world of English Language Teaching (ELT) is being transformed by Artificial Intelligence (AI) through the creation of language materials, automated feedback, and skills enhancement; however, the use of AI by senior educators has been under-researched. This qualitative descriptive case study, based on the Technology Acceptance Model (TAM), investigates senior English teachers’ perceptions of AI integration, especially with applications like ChatGPT and Grammarly, in secondary school English Language Teaching (ELT) practices. Four experienced English teachers were given open-ended questionnaires online, and the data were analyzed through theme analysis. The findings show five major themes: positive perceptions of AI as an adjunct tool; concerns over cheating, student reliance, and data security; average institutional readiness for AI-infused English Language Teaching (ELT), between 30% and 60% due to lack of digital literacy and infrastructure; needs for transparent, ELT-specific usage guidelines; and aspirations for the ethical and creative deployment of AI in educational contexts. The study concludes that focused professional development and policy support are key to addressing digital literacy disparities and fostering ethical AI adoption among senior teachers.